Should patients with brain implants undergo MRI?. (15th May 2018) - Erhardt, Johannes B; Fuhrer, Erwin; Gruschke, Oliver G; Leupold, Jochen; Wapler, Matthias C; Hennig, Jürgen; Stieglitz, Thomas; Korvink, Jan G
Abstract: Patients suffering from neuronal degenerative diseases are increasingly being equipped with neural implants to treat symptoms or restore functions and increase their quality of life. Magnetic resonance imaging (MRI) would be the modality of choice for the diagnosis and compulsory postoperative monitoring of such patients. However, interactions between the magnetic resonance (MR) environment and implants pose severe health risks to the patient. Nevertheless, neural implant recipients regularly undergo MRI examinations, and adverse events are rarely reported. However, this should not imply that the procedures are safe. More than 300 000 cochlear implant recipients are excluded from MRI, unless the indication outweighs the excruciating pain. For 75 000 deep brain stimulation (DBS) recipients quite the opposite holds true: MRI is considered an essential part of the implantation procedure and some medical centres deliberately exceed safety regulations, which they refer to as crucially impractical. Permanent MRI-related neurological dysfunctions in DBS recipients have occurred in the past when manufacturer recommendations were exceeded. Within the last few decades, extensive effort has been invested to identify, characterise and quantify the occurring interactions. Yet today we are still far from a satisfying solution concerning a safe and beneficial MR procedure for all implant recipients. To contribute, we intend to raise awareness of the growing concern, summon the community to stop absurdities and instead improve the situation for the increasing number of patients. Therefore, we review implant safety in the MRI literature from an engineering point of view, with a focus on cochlear and DBS implants as success stories of neural implants in clinical practice. We briefly explain fundamental phenomena which can lead to patient harm, and point out breakthroughs and errors made. Then, we end with conclusions and strategies to avoid future implants from being contraindicated in MR examinations. We believe that implant recipients should enter MRI, but before doing so, it should be made sure that the procedure is reasonable.